Tocilizumab in refractory Caucasian Takayasu's arteritis: a multicenter study of 54 patients and literature review. (June 2021) - Prieto-Peña, Diana; Bernabeu, Pilar; Vela, Paloma; Narváez, Javier; Fernández-López, Jesús C.; Freire-González, Mercedes; González-Álvarez, Beatriz; Solans-Laqué, Roser; Callejas Rubio, José L.; Ortego, Norberto; Fernández-Díaz, Carlos; Rubio, Esteban; et al.
Objective: To assess the efficacy and safety of tocilizumab (TCZ) in Caucasian patients with refractory Takayasu's arteritis (TAK) in clinical practice. Methods: A multicenter study of Caucasian patients with refractory TAK who received TCZ. The outcome variables were remission, glucocorticoid-sparing effect, improvement in imaging techniques, and adverse events. A comparative study between patients who received TCZ as monotherapy (TCZMONO ) and combined with conventional disease modifying anti-rheumatic drugs (cDMARDs) (TCZCOMBO ) was performed. Results: The study comprised 54 patients (46 women/8 men) with a median [interquartile range (IQR)] age of 42.0 (32.5–50.5) years. TCZ was started after a median (IQR) of 12.0 (3.0–31.5) months since TAK diagnosis. Remission was achieved in 12/54 (22.2%), 19/49 (38.8%), 23/44 (52.3%), and 27/36 (75%) patients at 1, 3, 6, and 12 months, respectively. The prednisone dose was reduced from 30.0 mg/day (12.5–50.0) to 5.0 (0.0–5.6) mg/day at 12 months. An improvement in imaging findings was reported in 28 (73.7%) patients after a median (IQR) of 9.0 (6.0–14.0) months. Twenty-three (42.6%) patients were on TCZMONO and 31 (57.4%) on TCZCOMBO : MTX ( n = 28), cyclosporine A ( n = 2), azathioprine ( n = 1). Patients on TCZCOMBO were younger [38.0 (27.0–46.0) versus 45.0 (38.0–57.0)] years; difference (diff) [95% confidence interval (CI) = -7.0 (-17.9, -0.56] with a trend to longer TAK duration [21.0 (6.0–38.0) versus 6.0 (1.0–23.0)] months; diff 95% CI = 15 (-8.9, 35.5), and higher c-reactive protein [2.4 (0.7–5.6) versus 1.3 (0.3–3.3)] mg/dl; diff 95% CI = 1.1 (-0.26, 2.99). Despite these differences, similar outcomes were observed in both groups (log rank p = 0.862). Relevant adverse events were reported in six (11.1%) patients, but only three developed severe events that required TCZ withdrawal. Conclusion: TCZ in monotherapy, or combined with cDMARDs, is effective and safe in patients with refractory TAK of Caucasian origin.